How economics shapes science - Stephan, Paula E. (Harvard University Press, 2012)
At a time when science is seen as an engine of economic growth, Paula Stephan brings a keen understanding of the cost-benefit calculations made by individuals and institutions as they compete for resources and reputation in scientific fields. She highlights especially the growing gap between the biomedical sciences and physics/engineering.